Perkuatan Lentur Pelat Lantai Tampang Persegi dengan Penambahan Tulangan Tarik dan Komposit Mortar - Hartono, Juandra; Satyarno, Iman; Triwiyono, Andreas (Jurnal Semesta Teknika, 2010)
Overloading of structures can cause failure. In order to continue using them, strengthening is required. In this research elastic strengthening was carried out on concrete floor plates by means of tensile reinforcement addition, and mortar composite additionto apply epoxy resin. Four reinforced concrete slabs, consisted of one control slab (PK), one monolith slab (PM), one strengthened slab (PPE) and one unstrengthened slab (PPTE). Specimen dimensions were 700 mm x 1500 mm x 60 mm for the PK, and 700 mm x 1500 mm x 100 mm for the others. Specimens were placed on a simply supported loading frame, and statically loaded at their mid-span. Numerical analysis using Response-2000 software package was carried out for comparison with the experiment al result. It was found out that the flexural capacity of the PK, PPE, PPTE and PM specimens are 5,99 kNm, 12,52 kNm, 13,87 kNm and 21,38 kNm, respectively. In comparison with that of thePK, flexural capacity of the PPE and PPTE specimens was found to increase by 109,019 % and 131,55 %, respectively. The increase of stiffness was 324,77 % and 430,21 % for the PPE and PPTE specimens, respectively. The ductility factor of the PPE and PPTE increase 29,63 % and 19,03 %, respectively . The PK and PM specimen s experienced flexural failure, while the PPE and PPTE specimens experienced debondingfailure.